Study on the Influence of Anasthesis Temperature and Time on Tiger Shrimp Survival Rate in Dry Transportation System - Rahman Karnila; Sam Herodian; Made Astawan; Rudy R Nitibaskara (PERTETA, 1999)
The objective of this research is tojind out the best temperature, lime and handling method for black tiger shrimp transportation with dry system. Anesthesis method was applied in this research by adopting gradual cooling ut the rate of 5